LB5 Is the duration of the preceding inter-pregnancy interval associated with offspring's size at birth? – analysis of a UK population-based cohort. (September 2018) - Ziauddeen, N; Roderick, PJ; Macklon, NS; Alwan, NA
Abstract : Background: Short and long intervals between pregnancies have been associated with increased risk of adverse birth outcomes including low birth weight and stillbirth. Birthweight is an indicator of the in-utero environment and a key early life risk factor for long-term health outcomes such as obesity and cardiovascular disease. The World Health Organization recommended in 2005 waiting at least 24 months after a live birth before getting pregnant again. There are no UK guidelines on birth spacing. We aimed to investigate the association between duration of the inter-pregnancy interval between successive live birth pregnancies and risk of having a small-for-gestational age (SGA) or large-for-gestational age (LGA) baby. Methods: A population-based cohort of prospectively collected routine healthcare data for antenatal care between January 2003 and September 2017 (total n=82 098 pregnancies) at University Hospital Southampton, Hampshire, UK was used. Records of women with their first two singleton live-birth pregnancies were analysed (n=15 922 women). Inter-pregnancy interval was defined as timing between a live birth and the next conception. SGA was defined as <10th percentile weight and LGA as >90th percentile weight for gestational age. Logistic regression was used to examine the association between risk of SGA or LGA and inter-pregnancy interval. The models were adjusted for maternal age, ethnicity, highest educational qualification, employment status, baseline maternal BMI, between pregnancy change in maternal BMI, smoking status at second pregnancy booking appointment and conception following infertility treatment. Sensitivity analyses was conducted adjusting for SGA or LGA in previous pregnancies. Results: Twelve percent of first pregnancy and 7% of second pregnancy births were SGA. Seven percent of first pregnancy and 13% of second pregnancy births were LGA. Three percent of women each had SGA and LGA babies in both pregnancies. Compared to an interval of 24–35 months, there was a lower risk of SGA birth in second pregnancy with an interval of 12–23 months (adjusted OR 0.82, 95% CI 0.69 to 0.98, p=0.03). The association remained after adjusting for previous outcome of SGA in sensitivity analysis. No association was observed between risk of SGA with intervals of <12 or ≥36 months or LGA and inter-pregnancy interval. Conclusion: An inter-pregnancy interval of 12–23 months was associated with lower risk of SGA, however the duration of the interval was not associated with LGA risk. In high-income countries with relatively healthy pregnant population, further research considering the potential advantages of shorter optimal interval between pregnancies than that recommended by WHO is needed. Acknowledgements: David Cable (Electronic Patient Records Implementation and Service Manager) at University Hospital Southampton NHS Foundation Trust for support in accessing the data used in this study.